Umbilical cord length and neurodevelopmental disorders, a national cohort study - Cathrine Ebbing; Anne Halmoy; Svein Rasmussen; Karen K. Mauland; Jørg Kessler; Dag Moster (PLoS ONE, 2025)
Introduction Adversities in fetal life are known risk factors for neurodevelopmental disorders (NDD). Despite the pivotal role of the umbilical cord, little is known about its associations to later NDD. Objective To estimate the associations between umbilical cord length and NDD (Attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), intellectual disability (ID), cerebral palsy (CP), epilepsy, impaired vision or hearing), and whether associations differed by sex. Materials and methods A prospective population-based cohort study including all liveborn singletons in Norway from 1999, through 2013 and followed up through 2019. Data were retrieved from The Medical Birth Registry of Norway and linked with other national health and administrative registries. Exposures were extreme umbilical cord length (empirical percentile <5th or ≥ 95th percentiles). Main outcome measures were NDD (ADHD, ASD, ID, CP, epilepsy, impaired vision or hearing). Associations with umbilical cord length were assessed using logistic regression. Results The cohort consisted of 858,397 births (51.3% boys). We identified 33,370 persons with ADHD (69.8% boys), 10,818 had ASD (76.0% boys), 5538 ID (61.4% boys), 2152 with CP (59.9% boys), 8233 epilepsy (55.0% boys), 900 impaired vision (boys 55.0%), and 11,441 impaired hearing (boys 52.8%). Cord length was positively associated with ADHD (OR 1.15; 95%CI 1.09–1.22), i.e., the risk increased with long cord and decreased with short cord, regardless of sex. A short cord was positively associated with ID (OR 2.42; 95%CI 2.17–2.69), impaired hearing (OR 1.41; 95%CI 1.29–1.54), and epilepsy (OR 1.31; 95%CI 1.18–1.46). CP was associated with both short and long cord (OR 1.31; 95% CI 1.07–1.61 and 1.34, 95%CI 1.13–1.60, respectively). There was no association between cord length and impaired vision. Conclusions This first population study finds that umbilical cord length is associated with NDD. The findings support the hypothesis that neurodevelopment and development of the umbilical cord share pathways.